Language and emotion: Content analysis of private digital writing in English - Edby, Yasmin Deviana; Seinsiani, Izzati Gemi (ELT Forum: Journal of English Language Teaching, 2025)
This study discusses the role of English as a foreign language in emotional regulation by an Indonesian multilingual writer in her private digital writing. Whereas most works on multilingual emotional expression focus on translanguaging, identity performance, or public discourse, this study analyzes a blog post written entirely in English but never published. In such cases, language choice cannot be explained with reference to audience expectations or self presentation. Drawing upon Pavlenko's (2006) notion of emotional distancing and supported by related research in affect labeling and expressive writing, this paper will try to analyze how the writer uses the English language to work out their intense emotional experiences, especially related to negative feelings, and the reasons they choose English, which is a foreign language, to express her negative feelings. The data comes from an unpublished blog post called Medium, combined with a semi structured interview with its author, who is a 22 year old university student. Thematic analysis was applied in mapping patterns of emotional reasoning and language beliefs. Results indicate that the writer severely expresses so much self criticism, loss, and bitter acceptance using strong negative words. This study also finds that English gives the writer psychological distance and cognitive control over emotions and is therefore perceived as less saturated with emotion compared to Indonesian. Thus, this writer can express vulnerable thoughts in English without getting too consumed by emotions, though English is still a foreign language to her compared to Bahasa Indonesia. The choice of English by this writer is driven inwardly by an internal need for emotional buffering and clarity rather than any consideration of public visibility or identity construction. This study offers a contribution to emotional sociolinguistics by bringing into focus the less focused function of monolingual foreign language usage in private writing. It underscores how that very particular language, even when not applied to public discourse, can become for multilinguals an individual affective strategy enabling them to write out their distress with more emotional strength.